Influence of local stress concentrations on the crack propagation in complex welded components - C. Fischer; W. Fricke (Fracture and Structural Integrity)
While a long stable crack propagation phase was observed during experiments of complex welded components, very conservative assessments of the fatigue life were achieved in the past. The difference was explained by the stress gradient occurring over the plate thickness. This paper deals with numerical crack propagation simulations which were performed for different geometrical variants. The variants differ related to global geometry, boundary conditions and weld shape. The analyses aim to investigate how the crack propagation is altered if the structural configuration gets more complex. In conclusion, the stress gradient over the plate thickness, the apparent plate thickness and the notch effect slows down the crack propagation rate if the same stress value being effective for fatigue appears at the weld toe. Thereby, the load-carrying grade of the weld, the weld flank angle and the geometrical configuration have an impact on both the notch effect and the local stress concentration.